Automation Testing Pada Aplikasi e-commerce Menggunakan Metode Equivalence Partitioning - Alie Shodiq Fathurrahman, Mochammad; Arifin, Jaenal (Institut Tekonologi dan Binisi Asia Malang, 2023)
In this era of development, the method of developing software systems has made a lot of progress, many terms and new methods have been raised to support the development of better and more effective software systems. One method that has emerged and is starting to gain popularity is quality assurance (QA), a process by which a software development team performs a series of tests on the system being developed. The quality assurance process is a key process carried out by developers to find errors and assess whether the developed system is optimal and there are no errors before it is marketed to users. There are many innovations in the quality assurance process, one of which is an automated testing system or automation testing. The advantages of automatic testing are carried out using the blackbox equivalence partitioning method to simplify the process of creating test scenarios. Automation testing also has tools such as Playwright, playwright is a tool that can run a script test automatically and display a report on the results of the tests carried out